Persepsi Mahasiswa terhadap Penerapan E-Learning dalam Pembelajaran - Jannah, Nur Miftahul; Hikmah, Nurul; Mardiati, Sueti; Amin, Muliaty; Angriani, Andi Dian (Al Asma: Journal of Islamic Education, 2024)
Since entering the industrial revolution 4.0 which began in the 21st century, technological developments have been accelerating and affecting various aspects of life including education. Current technological developments also have a significant influence on a person's perception to continue to adopt and integrate technological things in learning. The purpose of this research is to find out how mathematics education students perceive the use of e-learning in learning. This research is a quantitative descriptive research involving 31 students of the Mathematics Education undergraduate study program, Faculty of Tarbiyah and Keguruan UIN Alauddin Makassar, class of 2020-2022. Data collection was done through observation, questionnaire, and documentation. The data analysis used was descriptive analysis. The results showed that mathematics education students towards e-learning learning were in the high category. This indicates great potential for increased use, curriculum development, and technical and infrastructure support in an e-learning environment.